Attenuation of salt stress by lycopene on common bean seeds (Acta Scientiarum. Biological Sciences, 2022)
Salinity is a major abiotic stress that adversely affects several physiological and biochemical aspects of plants. Antioxidants can be used as a potential remediation mechanism to promote plant resilience. Therefore, the objective of the present study was to evaluate increasing doses of the antioxidant lycopene on the germination and initial growth of common bean seedlings under conditions of salt stress. Seeds were treated with the following lycopene concentrations: 0.018; 0.036; 0.072; 0.144; and 0.288 g L-1 and two controls (negative and positive) and evaluated under two growth conditions (without and with salt stress) for physiological quality and pigment content. Data were analyzed by completely randomized design, in 2 x 7 factorial (two growth conditions, with paper towel moistened with water or salt solution x seven treatments, including five lycopene doses and two controls), in four replicates of 50 seeds by concentration. With the results of the analysis of variance, growth conditions (without and with salt stress) were compared by the Tukey test (5%), and the effects of lycopene doses were analyzed by polynomial regression. Lycopene promoted tolerance of bean seeds to salt stress and had a positive influence on the attenuation of salt harmful effects to the initial growth of seedlings, mainly at the doses of 0.072 g L-1 and 0.144 g L-1.